Comparative Analysis of 3D Bladder Tumor Spheroids Obtained by Forced Floating and Hanging Drop Methods for Drug Screening - Amaral, Robson L. F.; Miranda, Mariza; Marcato, Priscyla D.; Swiech, Kamilla (Frontiers in Physiology, 2017)
Introduction. Cell-based assays using three-dimensional (3D) cell cultures may reflect the antitumor activity of compounds more accurately, since these models reproduce the tumor microenvironment better. Methods. Here, we report a comparative analysis of cell behavior in the two most widely employed methods for 3D spheroid culture, forced floating (Ultra-low Attachment, ULA, plates) and hanging drop (HD) methods, using the RT4 human bladder cancer cell line as a model. The morphology parameters and growth/metabolism of the spheroids generated were first characterized, using four different cell-seeding concentrations (0.5, 1.25, 2.5 and 3.75 x 104 cells/mL), and then, subjected to drug resistance evaluation. Results. Both methods generated spheroids with a smooth surface and round shape in a spheroidization time of about 48 hours, regardless of the cell-seeding concentration used. Reduced cell growth and metabolism was observed in 3D cultures compared to two-dimensional (2D) cultures. The optimal range of spheroid diameter (300-500 μm) was obtained using cultures initiated with 0.5 and 1.25 x 104 cells/mL for the ULA method and 2.5 and 3.75 x 104 cells/mL for the HD method. RT4 cells cultured under 3D conditions also exhibited a higher resistance to doxorubicin (IC50 of 1.00 μg/mL and 0.83 μg/mL for the ULA and HD methods, respectively) compared to 2D cultures (IC50 ranging from to 0.39-0.43). Conclusions. Comparing the results, we concluded that the forced floating method using ULA plates was considered more suitable and straightforward to generate RT4 spheroids for drug screening/cytotoxicity assays. The results presented here also contribute to the improvement in the standardization of the 3D cultures required for widespread application.